Integration of Open Educational Resources (OER) with D2L Brightspace - Fardadvand, Shahram (My University, 2025)
The integration of Open Educational Resources (OER) with Learning Management Systems (LMS) such as Moodle and Canvas is redefining course design by enabling educators to create accessible, flexible, and dynamic learning experiences. Explore how Pressbooks, an open-source publishing platform, improves LMS capabilities by simplifying the integration of Open Educational Resources (OER) into well-structured course designs. Pressbooks offers powerful export options for designing courses that combine chapters and materials from diverse OER sources. Educators can remix, adapt, and integrate content into unified course modules while retaining the interactivity and accessibility essential for today's learners. This guide demonstrates how Pressbooks empowers educators to build flexible courses tailored to their curriculum by embedding resources directly within D2L Brightspace. Educators can improve teaching by using Pressbooks' easy integration. This integration helps deliver content better and engages learners more. Examples of successful course designs will show how combining material from different Open Educational Resources (OER) improves teaching and learning.
Presented on March 11-12, 2025, at The Society for Teaching and Learning in Higher Education (2025 STLHE) Conference held virtually.
Keywords: Open Educational Resources (OER); Learning Management Systems (LMS); course design; Pressbooks; D2L Brightspace